Experiments on an induction type high speed wind tunnel driven by low pressure steam - Lilley, G. M.; Holder, D. W. (College of Aeronautics, Cranfield, 1949)
The performance of an induction type high speed wind tunnel driven by low pressure steam (up to 120lb. per sq.in. absolute) has been investigated up to a Mach number of about 1.7. It was found that by suitable design a range of Mach numbers could be attained over a wide range of supply pressures and steam quantities. Comparison with previous experiments in which compressed air was used to drive the tunnel show that the required steam and air pressure and quantities are comparable. These results imply that in many cases existing boiler plants can readily be adapted to drive high speed tunnels of useful dimensions. Continues …